Judicial reform as a tool for increase efficiency of legal protection of individuals - A. V. Malko; S. F. Afanasiev; V. A. Terekhin (Правоприменение)
The subject. The authors analyze the process and results of 30 years of reforming judicial activity in contemporary Russia, formulate and substantiate the conceptual foundations of promising transformations and specific proposals for continuing the reform, increasing the efficiency of the judicial system and protecting human rights, freedoms and legitimate in-terests.The purpose is to confirm or disprove hypothesis that the Russian judicial reform needs to be adjusted in order to remain the most important factor in building the rule of law and civil society.The research methodology includes the methods of analysis and synthesis, historical, com-parative legal and formal legal methods.The main results, scope of application. The court is one of the most democratic and civilized tools for resolving social conflicts and protecting human interests. Judicial reform is a con-ceptually formed, cardinal and progressive transformation carried out in the historical pe-riod in order to organize the optimal model of the judicial system and achieve maximum efficiency of its functioning to protect the rights and freedoms of the individual, the inter-ests of society and the state. The Russian court was transformed, became the real judiciary power and took its place in the state mechanism during the reform period. The judicial sys-tem was built on new principles, procedural legislation was updated, a number of other measures were taken to improve the status of the court and its role in society. It is necessary to generalize the existing practice and regulate all problematic aspects of the formation of the judicial corps at the legislative level. We need to make this process clear and transpar-ent. Justice as a social and legal value and a significant international goal of sustainable development should be implemented in Russian domestic policy and strategic projects. The strategy and tactics of digital transformation of judicial activity, more active introduction of modern tools in it, while ensuring human rights and freedoms in this process, are particu-larly in demand in the context of the coronavirus pandemic,The conclusion is made that judicial reform is the most important factor in building the rule of law and civil society. However, it has not been completed and its potential for social influence has not been exhausted. Therefore, conceptual foundations and specific proposals for further transformations, increasing the efficiency of the judicial system in order to protect human rights, freedoms and legitimate interests have been formulated and substantiated.